Measuring the Level of HRIS Governance Capability in the Automotive Financing Company Using COBIT 2019 - Naufal, Muhammad; Sutomo, Rudi (Universitas Bina Darma, 2024)
In response to the imperative advancements in information technology, companies strive to leverage it for a competitive edge. An automotive financing entity with over 4,000 employees encounters challenges in governing its Human Resources Information System (HRIS). Difficulties include employee service being negatively impacted by delayed HRIS computations, budgets growing faster than regulations, and branch employees not understanding HRIS. The organization intends to use the COBIT 2019 framework to assess its IT governance to address these issues. Based on qualitative interviews and literature reviews, data collection will identify relevant domain processes—APO03, APO06, APO011, APO07, and DSS06—to address the issues. The research reveals that APO03, APO06, APO011, and APO07 are